PENGARUH KESEHATAN DAN KESELAMATAN KERJA (K3) DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. JOLO INDAH KEDIRI - Rizky Fadhlia Ramadhan; Taufik Akbar; Ririn Wahyu Arida (Cahaya Ilmu Bangsa, 2024)
This research aims to determine the influence of occupational health and safety (K3) and work discipline on employee work productivity at PT. Jolo Indah Kediri. The research method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to PT employees. Jolo Indah Kediri and calculated using the SPSS Version 25 application. The population in this study were all employees at PT. Jolo Indah Kediri and 35 samples were obtained from saturated sampling calculations. Data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test, and R2 Coefficient of Determination Test. In the validity test, it is known that all statement items on the variables (X1, X2, and Y) have a significance value of 0.000 < 0.05, so that each variable is declared valid. Then in the reliability test it was discovered that each variable had a Cronbach's Alpha value > 0.60 so that the variable was declared reliable. Furthermore, in the t test it was found that all variables (work health and safety (K3) and work discipline) had a positive value and a significance of <0.05 so that it was stated that they partially had a significant effect on work productivity. Then in the F test the Sig value is known. for all variables together it is 0.000 < 0.05 and the value of Fcount > Ftable, it can be concluded that the variables of occupational health and safety (K3) and work discipline simultaneously influence employee work productivity at PT. Jolo Indah Kediri.